Mixed harvest : stories from the human past - Swigart, Rob (Berghahn Books, 2020)
"After millennia of wandering the earth with little impact, a universal, if inadvertent transition from hunting and gathering to agriculture and pastoralism was complete within a period of a few thousand years. Mixed Harvest tells the story of the Sedentary Divide, the most significant event since modern humans emerged. Before the Sedentary Divide, humans followed their food; afterward, everything the human diet had abandoned wild foods by domesticating, and irrevocably changing, plants and animals, staying in one place and keeping them close. Agriculture was so successful that religious and social belief systems evolved to enforce social inequality, exploitation of resources, constrained gender relations, and increasingly devastating conflict"--